2017
DOI: 10.1016/j.ijdevneu.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Does dual tasking ability change with age across childhood and adolescence? A systematic scoping review

Abstract: The aim of this literature search was to identify nature and extent of the evidence supporting the development of dual tasking skills in typically developing children. We systematically searched PsycINFO, Ovid and Pubmed for studies evaluating dual task performances of children and adolescents <18 years of age. 31 studies published in English from 1990 to 2016 were included. A descriptive analysis was used for data extraction and charting. Study findings reported that age influenced dual task performances unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…; Saxena et al . ). Considering that stability in most daily routine tasks is centrally processed together with cognitive and/or attentional tasks (Mezzacappa ; Schaefer ), such as walking while talking on the telephone and walking while holding delicate objects on hands, it seems to be important to study the effects of dual‐tasks on postural control.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Saxena et al . ). Considering that stability in most daily routine tasks is centrally processed together with cognitive and/or attentional tasks (Mezzacappa ; Schaefer ), such as walking while talking on the telephone and walking while holding delicate objects on hands, it seems to be important to study the effects of dual‐tasks on postural control.…”
Section: Introductionmentioning
confidence: 97%
“…; Saxena et al . ), our initial hypothesis was that the addition of a secondary task would increase postural sway during the primary task (STS), especially at the end of STS, which involves active body displacement against gravity and reduction of the base of support. Due to neuromotor impairments in Down syndrome, this increase will be more pronounced in this group.…”
Section: Introductionmentioning
confidence: 99%
“…However, temporal and spatial parameters can still improve around 11–15 years, which can be explained by the continuing development of the nervous system and the changes of the anthropometric characteristics (Hausdorff et al, 1985). During childhood, some inconsistent results in dual‐task conditions have also been obtained in postural control (Ruffieux et al, 2015) and walking performances (Schott and Klotzbier, 2018; Saxena et al, 2017; Schaefer et al, 2015). (Olivier et al (2008)) showed an improvement of standing in children aged 4–11 years while watching a movie.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date only few studies have investigated DT in typically developing children, who exhibiting typically greater vulnerability to Dual Task Effects (DTE). The evidence supporting the effects of age on the ability to coordinate a motor and a cognitive task show inconsistent results in children and adolescents, where the DTE – if computed at all – range from either being lower or comparable or higher in younger children (4–6 years) than in older children (7–12 years), adolescents and adults ( Whitall, 1991 ; Huang et al, 2003 ; Cherng et al, 2007 ; Schaefer et al, 2010 , 2015 ; Anderson et al, 2011 ; Krampe et al, 2011 ; Boonyong et al, 2012 ; Beurskens et al, 2015 , 2016 ; Hagmann-von Arx et al, 2016 ; Hinton and Vallis, 2016 ; Chauvel et al, 2017 ; see also Saxena et al, 2017 for an excellent review). For instance, Boonyong et al (2012) found that children aged 5 and 6 years, and 7–16 years, use a more careful strategy (e.g., reduced gait speed and step length), than that of adults during obstacle crossing while performing an Auditory Stroop-Task.…”
Section: Introductionmentioning
confidence: 99%
“…Its main prediction is that maintaining kinematic gait parameters should be less efficient in DT than ST conditions, which in turn depends on the complexity of the selected task as well as the development of the selected cognitive domain. Recent reviews by Ruffieux et al (2015) and Saxena et al (2017) examining balance and walking performance under dual-task conditions discuss several methodological issues in existing studies at length. Saxena et al (2017) suggest seven criterions to improve overall quality of studies: appropriateness of single tasks (ST), equation of tasks, calculation of DTEs, DTE for each ST, randomization of task order, practice effects, and clear instructions.…”
Section: Introductionmentioning
confidence: 99%